Membangun Sistem Integritas Untuk Pemberantasan Korupsi Dalam Sistem Peradilan Pidana Indonesia - Masyhudi Masyhudi (Fakultas Hukum Universitas Islam Indonesia, 2019)
This research aims to analyse and observe: first, the current system of corruption eradication in the Indonesia's positive law perspective; second, the strategy of the Indonesian government to eradicate the corruption in future; and third, the concept of an Integrity System to eradicate the corruption ininvestigations conducted by the Prosecutors, Police and KPK in Indonesia. The research method used is normative juridical legal research using a legal and conceptual approach. The results of the study showed that first, the system of corruption eradication in Indonesian positive law currently has placed KPK as a leader, causing disharmony among the law enforcers; second, the Indonesian government's strategy to eradicate corruption in the future can be done through an integrity system within the scope of the KPK, the Police and the Prosecutor's Office; third, the concept of the Integrity System for corruption in investigation by the Attorney General's Office, the Police and the Corruption Eradication Commission is carried out by establishing the Integrity Court. This integrity system must be able to position the three institutions as the independent Anti-Corruption Bodies.